Pengaruh Suhu dan Kelembaban Terhadap Rasio Kelembaban dan Entalpi (Studi Kasus: Gedung UNIFA Makassar) - Ahmad Nadhil Edar; Arinda Wahyuni (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2021)
Temperature affects humidity. The interaction of temperature and humidity also directly affects the health and well-being of humans. The relative humidity (RH) of the air is anindication of how much water vapor is in the air at a particular temperature compared with how much water vapor the air could actually hold at that temperature. Air at 100 % relativehumidity holds the maximum amount of water possible at that particular temperature and is said to be saturated. Therefore, air at 50% relative humidity, regardless of temperature, isholding half of its total possible water capacity. In essence, cold air cannot hold as much water vapor as warm air. In a closed environment such as a display case, there will be a fixedamount of water vapor, referred to as the absolute humidity. If the temperature inside the case falls then the relative humidity will rise. If the temperature rises the relative humidity will fall. Such changes in relative humidity could be caused by many factors including direct sunlight, spotlights and air-conditioning failures Research carried out by experimental studies that we can get the humidity ratio and specific enthalpy in a kind of rooms either using The Psychrometric Chart and The formula. The specific humidity or humidity ratio of an air sample is the ratio of the weight of water vapor contained in the sample compared to the weight of the dry air in the same sample. Enthalpy is the amount of heat (energy) in the air per unit mass. Enthalpy is the total amount of energy present in the air, both from air and water vapor contained therein. And, Specific enthalpy of moist air is defined as the total enthalpy of the dry air and the water vapor mixture - per unit mass of dry air.